EFFECTIVENESS OF ALTERNATE NOSTRIL BREATHING EXERCISE ON STRESS AMONG STAFF NURSES WORKING AT SELECTED HOSPITAL - Mrs. Aleena Meety Lal. A; Mrs. T.S. Vinnoli; Mrs. Rosy. P; Mrs. K. Bindhu; Mrs. R. Yuvashree; Mrs. Gayathri. T; Mr. K. Santhosh (The Bioscan, 2024)
Nursing is widely recognized as a high-stress profession. Work stress has a negative effect on nurses' health and the quality of patient care. The objective of this study was to assess stress levels in staff nurses and evaluate the effectiveness of alternative nostril breathing exercises. Fifty-eight staff nurses from Panimalar Medical College Hospital and Research Institute were selected to participate in the study using a non-probability purposive sampling technique. A pretest, single group, and posttest design was used. Using the TAWS-16 measurement tool to assess stress levels. The results of the pre- test indicated moderate stress in 96.56% of nurses, slight stress in 1.72% and severe stress in 1.72% of nurses after using an alternative method of practicing nostril breathing. Post-test results revealed that 98.27% of nurses reported slight stress and 1.73% moderate stress. with no reports of severe stress. 05) However, no significant relationship was found between post-test stress levels and demographic variables. The findings highlight the potential of alternative nasal breathing exercises as a simple strategy. non-invasive to reduce stress among nurses.